2017
DOI: 10.1017/s136898001700163x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy, safety and acceptability of a fish protein isolate in the nutrition of children under 36 months of age

Abstract: The FPi was well accepted and there was no significant difference in growth between both groups. FPi is a potential source of animal protein at lower cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Fish protein offers the same protein quality as other animal source proteins such as meat, eggs, chicken, or liver. A cluster randomised controlled trial that assessed the effect of a fish protein isolate (FPi), administered over six months, on the growth of children aged 6–36 months compared with a standard meal (with animal protein derived from beef, chicken, eggs or liver) found that fish protein was just as effective in improving growth (HAZ) of children as a standard meal [ 35 ]. Fish consumption has shown an improvement in linear growth among children in other studies as well [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fish protein offers the same protein quality as other animal source proteins such as meat, eggs, chicken, or liver. A cluster randomised controlled trial that assessed the effect of a fish protein isolate (FPi), administered over six months, on the growth of children aged 6–36 months compared with a standard meal (with animal protein derived from beef, chicken, eggs or liver) found that fish protein was just as effective in improving growth (HAZ) of children as a standard meal [ 35 ]. Fish consumption has shown an improvement in linear growth among children in other studies as well [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was only one study in Lima, Peru, that assessed the efficacy of fish in the early complementary feeding to improve growth in infants and young children in low-income countries to which we could compare our results [ 35 ]. However, the Peru study compared the FPi to a standard diet with animal protein derived from beef, chicken, eggs, or liver among children aged 6–36 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…El crecimiento de los niños fue similar, así como el consumo; no reportándose eventos adversos. El costo de los almuerzos con FPi fue entre 20 % a 40 % menor que la dieta estándar con otras proteínas de origen animal (20) . De manera similar, el presente estudio en niños mayores de tres años mostró una adecuada aceptabilidad del uso de proteína purificada de pescado en la alimentación de los niños, sobre todo en los menores de seis años.…”
Section: Discussionunclassified